Evidence for restricted Loch Lomond Stadial plateau ice in Glen Turret and implications for the age of the Turret Fan. Issue 1 (February 2017) - Boston, Clare M.; Lukas, Sven
Abstract: Despite a wealth of research on the patterns and timing of glaciation in Glen Roy over the last 150 years, glacial events within Glen Turret remain heavily debated. These debates centre on the extent and source of Loch Lomond Stadial (Younger Dryas) ice in Glen Turret, and the implications for the age and genesis of the Turret Fan. Here we present details of recent systematic geomorphological mapping of Glen Turret and the neighbouring valleys to the north and east. The geomorphological evidence recorded indicates a plateau icefield style of glaciation centred on the Carn Dearg plateau, of which the Turret Glacier was an outlet. A morphostratigraphical approach is used to identify a relative chronology of glacial events, and suggests that the Turret Fan may have formed prior to the Loch Lomond Stadial. A reconstruction of the Carn Dearg plateau icefield is presented, which was connected to the larger Monadhliath Icefield to the east. Equilibrium line altitudes for the outlet glaciers range from 560 ± 20 m to 646 ± 20 m and are comparable with those calculated for surrounding regions. This research suggests that the Turret Fan is predominantly an older feature that was deposited by a more extensive plateau ice-sourced Turret Glacier prior to the Loch Lomond Stadial, most likely during or immediately after deglaciation of the last ice sheet.